2004
DOI: 10.1016/s0022-2828(04)00085-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a KCNQ1/KVLQT1 polymorphism in Asian families with LQT2: implications for genetic testing

Abstract: Congenital long QT syndrome (LQTS) is a genetic disease that predisposes affected individuals to arrhythmias, syncope, and sudden death. Mutations in several ion channel genes have been discovered in different families with LQTS: KCNQ1 (KVLQT1, LQT1), KCNH2 (HERG, LQT2), SCN5A (LQT3), KCNE1 (minK, LQT5), and KCNE2 (MiRP1, LQT6). Previously, the P448R-KVLQT1 missense mutation has been reported as an LQT1-causing mutation. In this report, we demonstrate the presence of the P448R polymorphism in two, unrelated Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…While in the AFR, AMR and EUR populations, this locus was a high conservational locus, with a C allele frequency 1. Sharma et al confirmed that KCNQ1-P448R most likely represents a benign polymorphism with no detectable changes in the current kinetics or expression level compared to the WT channel, and further that the identified polymorphism was ethnic specific [39]. We also identified G643S, as a MAF of 0.02 in SUNDS cohort, while Tester et al found 1 case among 173 Sudden Unexplained Death decedents in America [40].…”
Section: Discussionsupporting
confidence: 62%
“…While in the AFR, AMR and EUR populations, this locus was a high conservational locus, with a C allele frequency 1. Sharma et al confirmed that KCNQ1-P448R most likely represents a benign polymorphism with no detectable changes in the current kinetics or expression level compared to the WT channel, and further that the identified polymorphism was ethnic specific [39]. We also identified G643S, as a MAF of 0.02 in SUNDS cohort, while Tester et al found 1 case among 173 Sudden Unexplained Death decedents in America [40].…”
Section: Discussionsupporting
confidence: 62%
“…Thus, the identification of risk factors among LQTS populations with similar mutations may be important for risk-stratification in this genetic disorder. Ethnic-specific polymorphisms on the LQTS-related genes have been described in previous reports 8-15,25-27. Notably, Ackerman et al8 studied 744 healthy black, white, Asian and Hispanic subjects and reported 49 distinct amino acid-altering variants of four LQTS-related potassium channel genes.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, ethnic-specific SNPs have been recognized as important in the correct diagnosis and clinical management of LQTS suspected patients. In one report, a previously established KCNQ1 mutation, P488R, was found to be a common polymorphism in 14% of healthy Chinese volunteers after a healthy child of a proband was mistakenly diagnosed with LQTS while his undiagnosed brother was later found to have a novel HERG mutation 27. Therefore, diagnosis based on genotyping requires correct discrimination of genetic polymorphisms from pathologic mutations, which may be confounded by ethnic genetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…No mutations were found in KCNE1 or KCNJ2. However, one rare KCNQ1 variant (p.P448R, three cases) appeared a common, ethnic-specific polymorphism [44], whereas the mutations p.V279M, p.R885C and p.S1040G in KCNH2 (three cases in total) exhibited biophysical properties indistinguishable from wildtype [45] and are probably benign variants. For the remaining five cases clear functional effects have been found [43,45].…”
Section: Cardiac Potassium Channel Mutationsmentioning
confidence: 93%